The Influence of Prices and Products Customer Satisfaction - Helmiyanur, Helmiyanur; Sampurnawati, Sampurnawati; Syamsuddinnor, Syamsuddinnor; Sucipto, Sucipto; Jahri, Muhammad; Meyandie Nasution, Muhammad Darwis (Hut Publication Business and Management, 2025)
This research includes quantitative descriptive research. The aim is to determine the influence of price (X1) and product (X2) on consumer satisfaction (Y). Where the object of the research is the Acil Enor Canteen which is one of the School Canteens at SMA Negeri 13 Banjarmasin. The population is all students at SMA Negeri 13 Banjarmasin with a total of 713 people. Through the Slovin Formula, the sample size of this study was obtained for 88 students with an error rate of 10%. The data collection technique uses a questionnaire with the Likert Scale and the purposive sampling method. Meanwhile, the data analysis uses Multiple Linear Regression with the SPSS 26 tool. The results of this study show that Price has a significant effect on Consumer Satisfaction at the Acil Enor Canteen, by 37.75%. Products have a significant effect on Consumer Satisfaction at the Acil Enor Canteen by 63.23%. Then Price and Product have a significant effect together on Consumer Satisfaction at Acil Enor Canteen by 52,89%.